ANALISIS SALURAN PEMASARAN SELADA HIDROPONIK DI POJOK SAYUR KECAMATAN MARTAPURA KABUPATEN OKU TIMUR - Iman Sulaiman, Andri Irawan, Neng Karmila, Leni Sabrina, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2024)
Cultivating vegetables with a hydroponic system is one way to improve the quality of vegetables, one of which is green lettuce. Green lettuce has good benefits for the body. This study aims to analyze the marketing channels of hydroponic lettuce. This research was conducted at the hydroponic vegetable business